Limitations on the application of the principle of integral reparation in decisions of the Council of State: diverging stances from the Inter-American Court of Human Rights - Zabala Lozano, Daniel Eduardo; Rodríguez Nuñez, Annie Julieth (DIXI, 2024)
In the present article, the aim is to conceptually clarify how comprehensive reparation is determined and structured from the perspective of various authors, and its application according to the standards of the Inter-American Commission on Human Rights and the Colombian Council of State, in order to carry out the process of comprehensive reparation for victims in an appropriate manner and ensure a successful process for the parties involved. Following this, the shortcomings, limitations, and requirements for applying this principle are identified. A qualitative research was conducted, addressing the concept of comprehensive reparation in the field of international law, transitional justice, and state responsibility. A descriptive and qualitative approach is used to analyze jurisprudence and the guarantees of victims, utilizing an analysis matrix that compiles opinions from the Council of State and concepts from the Inter-American Court of Human Rights. The objective is to evaluate the effectiveness of comprehensive reparation in Colombia, considering the validity of the law in relation to legality, in order to understand different realities through the interpretation of facts and documentary triangulation. The focus is especially on the rulings of the Council of State to assess the principle of equality in comprehensive reparation for victims of the armed conflict.